Reproduction of tank goby(Glossogobius giuris) in Ujung Pangkah Waters, East Java - . Sulistiono (Jurnal Akuakultur Indonesia)
Tank goby (Glossogobius giuris) is a commonly fish found in coastal area. This study was aimed to investigate reproduction of the fish. Samples were collected from July to December 2005 from fish caught by fishermen using gill net and trap net in Ujung Pangkah Waters. Analysis was done to estimate sex ratio, gonad maturity, gonado somatic index, fecundity, and oocyte diameter. During the observation, the tank goby fish was 198 individual consisted of 112 male and 86 female fish varied 63‒230 mm in total body length. Sex ratio was around 1:1.1. First maturity gonad of male was 111‒134mm and female was 87‒110 mm total body length, respectively. According to gonad maturity stage and gonado somatic index, the fish was estimated to spawn from July to December. During July and August, the gonad maturity stage and gonado somatic index were higher indicating a lot of spawning fish during those months. Fecundity was 10,640‒150,639eggs and oocyte diameter was 49‒372 µm. Based on the oocyte distribution, the fish was estimated apartial spawner.